2012
DOI: 10.1371/journal.ppat.1002831
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analysis of Specific Metal Chelating Inhibitor Binding to the Endonuclease Domain of Influenza pH1N1 (2009) Polymerase

Abstract: It is generally recognised that novel antiviral drugs, less prone to resistance, would be a desirable alternative to current drug options in order to be able to treat potentially serious influenza infections. The viral polymerase, which performs transcription and replication of the RNA genome, is an attractive target for antiviral drugs since potent polymerase inhibitors could directly stop viral replication at an early stage. Recent structural studies on functional domains of the heterotrimeric polymerase, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
279
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(300 citation statements)
references
References 44 publications
21
279
0
Order By: Relevance
“…Structural studies have now revealed new opportunities for drug discovery that target the essential endonuclease activity of the virus (24)(25)(26). In the current study, we had two primary goals; to confirm that the known endonuclease inhibitor L-742,001 targets the enzyme within the intact virus by generating resistant mutants, and to survey the resistance potential of the endonuclease by characterizing the sites of mutation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Structural studies have now revealed new opportunities for drug discovery that target the essential endonuclease activity of the virus (24)(25)(26). In the current study, we had two primary goals; to confirm that the known endonuclease inhibitor L-742,001 targets the enzyme within the intact virus by generating resistant mutants, and to survey the resistance potential of the endonuclease by characterizing the sites of mutation.…”
Section: Discussionmentioning
confidence: 99%
“…The mutation appears to adjust the two-metal coordination geometry and weaken the binding of the distal Mn 2+ . The distal and proximal Mn 2+ ions are coordinated by two and four side chains, respectively, which explains their different binding affinities (24). As regards the I79L mutation, this residue is adjacent to the two-metal locale and can potentially impact its conformation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, a recent structural study showed that several known endonuclease inhibitors, including four diketo compounds and a green tea catechin, bind to the endonuclease active site of the PA protein [44]. All these inhibitors chelate the two critical manganese ions in the active site of the enzyme, although some differences are noted in the overall ligand ordination of these compounds.…”
Section: Structures Of the Rnp Protein Componentsmentioning
confidence: 99%